2008
DOI: 10.1590/s0102-86502008000200016
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial window used in the diagnosis of cardiac injury

Abstract: Purpose:The purpose of the present study is to analyze the results of subxiphoid pericardial window (SPW) and transdiaphragmatic pericardial window (TDP) procedures comparing the two techniques. Methods: During the period of January, 1994 to December, 2004, at UNICAMP, 245 patients underwent a pericardial window (PW) procedure to evaluate the possibility of cardiac injury. We reviewed the medical records of those patients in order to compare both procedures. Results: Two hundred and seven patients (84.5%) unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This wide variation reflects the proportion of gunshot wounds (GSWs) included in a particular series. Patients with penetrating thoracoabdominal injuries have a 20–30 per cent risk of cardiac injury where the tract overlies the cardiac silhouette.…”
Section: Introductionmentioning
confidence: 99%
“…This wide variation reflects the proportion of gunshot wounds (GSWs) included in a particular series. Patients with penetrating thoracoabdominal injuries have a 20–30 per cent risk of cardiac injury where the tract overlies the cardiac silhouette.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the incision made through performing this technique is smaller compared to the incision made for pericardial window, which may explain the zero rates of mortality, morbidity, infection, and complications. Recent studies recommend the pericardial window for a quick diagnosis of cardiac injury, as several researchers have presented their own account of performing the pericardial window technique for diagnosing cardiac injury in patients with stable conditions 2224. According to the majority of these studies, pericardial window is a standard technique, as it helps to detect or rule out cardiac injuries and is associated with the lowest morbidity rates, even if the gastrointestinal tract has been identified as a source of contamination 22…”
Section: Discussionmentioning
confidence: 99%
“…The stab wound is considered less severe than that produced by gunshots and is thus associated with a better prognosis 4,9,17,30,36 . Spencer Neto et al 36 drew attention to this issue by mentioning the probable selection of patients arriving with vital signs to Table 4 -Table 4 - Table 4 - Table 4 - Table 4 the operating room and therefore with less myocardial damage. His hypothesis is confirmed when analyzing violent deaths in the state of Pernambuco in 1991, where 70% of trauma deaths were produced by firearms.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Of these, 63.4% received between one and three units of packed red blood cells. Spencer Neto et al 36 concluded that patients who required more than three units of packed red blood cells in the pre and trans-operative periods had a higher relative risk of death; those who did not require transfusion, survived. Reversely, in our series there was no time to require transfusion in 20 cases and mortality reached 40%.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%